Ann Quin, object relations, and the (in)attentive reader. Issue 2 (1st February 2021) - Powell, Josh
ABSTRACT: Taking as its starting point her reading of Harry Guntrip's 1968 book on object-relations psychoanalysis, this article considers the role that experiences of mental or emotional absence play in Ann Quin's fiction. It begins by looking at Guntrip's account of the schizoid personality, using the theory he outlines as a lens through which to view the behaviour of Quin's characters. It then moves away from a question of Quin's characters to one of how she conceptualised her readers. Quin's writing, it argues, is concerned with the (in)capacity of her characters to attend to the world around them, but also the ways in which her readers attend to the printed words that confront them when they open one of her books. Finally, the article considers Quin's conceptualisations of readerly behaviour in the light of some recent critical work on modernist constructions of the reader.